Utilisation of pretreated oil palm empty fruit bunch fibres as substrate for acetone-butanol-ethanol fermentation by Clostridium spp - Ibrahim, Mohamad Faizal (2013)
Oil palm empty fruit bunch (OPEFB) is the most abundant lignocellulosic biomass in Malaysia produced by the palm oil industry and can be used as an alternative carbon source for fermentation. This abundant renewable resource of lignocellulosic biomass is not yet well utilised for beneficial and useful product. Since the world now is facing with the limited resource of fossil fuel, a study on the utilisation of this lignocellulosic biomass into production of alternative renewable biofuel is necessary in order to reduce our dependency on fossil fuel. In this work, the conversion of OPEFB fibres into sugar monomers was performed using formulated crude cellulases cocktail prior to ABE fermentation. The crude cellulase cocktail was produced by Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 using OPEFB fibres pretreated with 2% NaOH with autoclave, which were composed of 59.7% of cellulose, 21.6% of hemicellulose and 12.3% of lignin. Approximately 0.8 U/mL of FPase, 24.7 U/mL of CMCase and 5.0 U/mL of βglucosidase were produced by T. asperellum UPM1 at a temperature of 35°C and at initial pH 7.0. A 1.7 U/mL of FPase, 24.2 U/mL of CMCase, and 1.1 U/mL of βglucosidase were produced by A. fumigatus UPM2 at a temperature of 45°C and at initial pH 6.0. The crude cellulase was best produced at 1.0% of substrate concentration for both T. asperellum UPM1 and A. fumigatus UPM2. The hydrolysis percentage of pretreated OPEFB fibres using 5% of crude cellulase loading from T. asperellum UPM1 and A. fumigatus UPM2 were 3.33% and 19.11%, respectively. Formulation of crude cellulases cocktail produced by T. asperellum UPM1 and A. fumigatus UPM2 improved the hydrolysis percentage to approximately 25.56% using the same enzyme concentration. The maximum hydrolysis percentage achieved was 73% with reducing sugars concentration equivalent to 30 g/L and it was comparable when using commercial cellulase (Celluclast) that produced 31 g/L of reducing sugars. The two–step process of acetone–butanol–ethanol (ABE) fermentation by local isolate EB6 produced 2.61 g/L of total ABE while Clostridium acetobutylicum ATCC 824 produced 2.25 g/L of total ABE using 20 g/L of fermentable sugars derived from pretreated OPEFB fibres. ABE fermentation by Clostridium butyricum EB6 was not recommended for butanol production because it produced more ethanol (1.24 g/L) than acetone (0.69 g/L) and butanol (0.68 g/L). C. acetobutylicum ATCC 824 produced higher butanol (1.69 g/L) compared to acetone (0.37 g/L) and ethanol (0.19 g/L). A higher total ABE (2.93 g/L) was obtained in a fermentation using 20 g/L of glucose with buffer compared to without buffer that produced 1.34 g/L of total ABE by C. acetobutylicum ATCC 824. Approximately 8.77 and 9.15 g/L of total ABE were produced from fermentation using 40 g/L of glucose with and without buffer with butanol concentration of 5.33 and 5.37 g/L, respectively. The study found that by increasing the initial pH values, the formation of acids especially butyric acid formation were increased. In addition, increased the buffer concentration to 0.2 M at initial pH 6.0 resulted in acids accumulation of 16.83 g/L but reduced the total ABE production to 1.36 g/L. Higher buffer concentrations were not favourable for butanol production but enhanced the formation of other solvents (acetone and ethanol). Simultaneous saccharification and ABE fermentation (simultaneous process) using pretreated OPEFB fibres as substrate was further conducted in order to reduce the number of steps involved in bioconversion of cellulosic biomass into ABE. In this study, the saccharification process was tested at the condition similar to the ABE fermentation. The fermentable sugars (31.58 g/L) was comparable as in normal saccharification process. The simultaneous process by C. acetobutylicum ATCC 824 produced 4.45 g/L of ABE with butanol concentration of 2.75 g/L, while the total sugars consumption was equivalent to 25 g/L. This fermentation generated a butanol yield of 0.11 g/g and ABE yield of 0.18 g/g which were higher than ABE fermentation using 25 g/L of fermentable sugars from pretreated OPEFB fibres (two–step process). The simultaneous process by C. butyricum EB6 produced a similar ABE concentration when compared to the two–step process. Furthermore, both C. acetobutylicum ATCC 824 and C. butyricum EB6 produced more cumulative hydrogen in the simultaneous process compared to the two–step process.